Aristotle's Poetics in Renaissance England - Lazarus, M (2013)
This thesis brings to light evidence for the circulation and first-hand reception of Aristotle's Poetics in sixteenth-century England. Though the Poetics upended literary thinking on the Continent in the period, it has long been considered either unavailable in England, linguistically inaccessible to the Greekless English, or thoroughly mediated for English readers by Italian criticism. This thesis revisits the evidentiary basis for each of these claims in turn. A survey of surviving English booklists and library catalogues, set against the work's comprehensive sixteenth-century print-history, demonstrates that the Poetics was owned by and readily accessible to interested readers; two appendices list verifiable and probable owners of the Poetics respectively. Detailed philological analysis of passages from Sir Philip Sidney’s Defence of Poesie proves that he translated directly from the Greek; his and his contemporaries' reading methods indicate the text circulated bilingually as standard. Nor was Sidney’s polyglot access unusual in literary circles: re-examination of the history of Greek education in sixteenth-century England indicates that Greek literacy was higher and more widespread than traditional histories of scholarship have allowed. On the question of mediation, a critical historiography makes clear that the inherited assumption of English reliance on Italian intermediaries for classical criticism has drifted far from the primary evidence. Under these reconstituted historical conditions, some of the outstanding episodes in the sixteenth-century English reception of the Poetics from John Cheke and Roger Ascham in the 1540s to Sidney and John Harington in the 1580s and 1590s are reconsidered as articulate evidence of reading, thinking about, and responding to Aristotle's defining contribution to Renaissance literary thought.